IMPLEMENTASI LEAN THINKING UNTUK MENURUNKAN WAKTU TUNGGU PELAYANAN OBAT DI INSTALASI FARMASI RAWAT JALAN, RUMAH SAKIT PANTI RINI - Denny Widhiyanto Yanong; Erna Kristin; Firman (Journal of Health Service Management, 2023)
Background: Panti Rini Hospital is trying to improve service quality, one of which is in the Outpatient Pharmacy Installation. There are several problems in the Outpatient Pharmacy Installation in the drug service process until the patient receives the drug.Objective: Implementing lean thinking to reduce waiting time for drug services at the Outpatient Pharmacy Installation at Panti Rini Hospital. In particular, it will identify waste, implement solutions to it, and analyze drug service waiting times before and after implementing lean thinking at the Outpatient Pharmacy Installation at Panti Rini Hospital.Method: This type of action research consists of 1) The stage of preparing instruments and permits; 2) The preparation stage of data collection prior to intervention and action planning, conducting interviews, direct observation, focus group discussions with pharmacy staff and hospital IT staff and debriefing regarding the relationship between service flow and waiting time; 3) The stage of implementing lean thinking in dealing with waste; 4) The evaluation stage after the intervention by calculating the delay time at each sub-process point, calculating the lead time, cycle time, VAR.Results: The dominantly identified waste in the drug service process is waste of waiting, extra processing, motion, defects, and inventory. The solution to overcome this waste that is implemented is the use of an IT system. The impact was that the lead time for compounding recipes decreased from 85 minutes to 52.9 minutes and for non-compounding recipes from 37.6 minutes to 19.8 minutes. There is an increase in VAR (Value Added Ratio) of 24% for compounding electronic recipes and 25% for non-compounding electronic recipes. The results of the Independent Samples T-Test for compounding recipes showed that p=0.00 (p<0.05), and the results of the Mann-Whitney U Test for non-compounding recipes showed that p=0.00 (p<0.05), so the results were significant.Conclusion: Implementing Lean Thinking can increase the efficiency of the drug service process, thereby reducing waiting time at outpatient pharmacy installations.